Obesidade infantil na escola: uma revisão de literatura - Iannuzzi, Ieda Vasconcelos (Brasil, 2023)
The general objective of this research was to investigate in the literature which are the main risk factors associated with obesity in students aged between five and fifteen years in public schools in Brazil. And as specific objectives: Carry out searches in the databases considering established descriptors and inclusion and exclusion criteria; Identify the main risk factors found in the selected literature, Check the possibilities of dialogues between school and prevention of childhood obesity. The study consisted of a narrative review that analyzed the risk factors associated with obesity in public elementary school students in Brazil between 2013 and 2023. The review adopted a more descriptive and interpretive approach than a traditional systematic review, allowing for a more comprehensive analysis. comprehensive review of available studies on the subject. Among these twenty-one studies selected a priori, after a subsequent selection step, only eight of the twenty-one studies were considered adequate and relevant for the review, providing an initial evidence base for the analysis of risk factors associated with obesity in this area. population. However, during a more rigorous analysis, applying more specific criteria, two additional studies were excluded, resulting in a total of six studies out of eight that fully met the pre-defined criteria and were finally selected for inclusion in the narrative review. The analyzed studies pointed to a series of risk factors, including individual, behavioral, social and environmental aspects, which contribute to the increase in the prevalence of obesity in this population.